Answer:vf
Step-by-step explanation:
Answer:
t = 3
Step-by-step explanation:
Given
- 3 (t - 2) + 7t = 9t - 9 ← distribute left side and simplify
- 3t + 6 + 7t = 9t - 9
4t + 6 = 9t - 9 ( subtract 9t from both sides )
- 5t + 6 = - 9 ( subtract 6 from both sides )
- 5t = - 15 ( divide both sides by - 5 )
t = 3
Answer:
t = 3.
Step-by-step explanation:
-3(t - 2) + 7t = 9t - 9 Distribute the -3 over the parentheses:
-3t + 6 + 7t = 9t - 9 Subtract 9t from both sides:
-3t - 9t + 7t + 6 = -9 Subtract 6 from both sides:
-3t - 9t + 7t = -9 - 6
-5t = -15
t = -15/-5
t = 3 (answer).
Actual way to solve it